The Palgrave Handbook of Radical Left Parties in Europe
XXXIV, 768 p. 5 illus., 2 illus. in color.
Keywords: This profound and insightful handbook aims to promote critical reflection on the way we conceptualise and study the radical left and to advance research by asking new questions. Radical left parties in Europe have been the subjects of significant study in the last decade, aided by the demonstrable success of newer parties like the Greek Syriza and Spanish Podemos, as well as the persistence of more established actors like the German Die Linke. Nevertheless, the emergent literature remains patchy and many elements of the party family still poorly understood. This handbook brings together a range of leading analysts to provide a definitive compendium, one that provides both students and scholars with an informative and easy-to-use guide to the radical left in Europe. Through utilising a common analytical framework to analyse the radical left in 19 European countries (within and outside the EU), the Palgrave Handbook of Radical Left Parties in Europe provides a wealth of comparable data on a wide number of cases to provide a sound basis for future studies. This rigorous comparative framework, allied with the unprecedented in-depth overview of the development of the European radical left over the past two decades, makes this handbook an essential starting place for those interested in all aspects of the radical left as a party family. Fabien Escalona is Research Associate at Sciences Po Grenoble, France, and journalist of the French online journal Mediapart. His publications include La reconversion partisane de la social-démocratie européenne (2018), European social democracy during the global economic crisis (co-edited with D. J. Bailey et al, 2014), and The Palgrave Handbook of Social Democracy in the European Union (co-edited, 2013). Daniel Keith is Senior Lecturer in Politics at the University of York, UK. His research interests include radical left politics, populist parties and internal party organisation. He has recently published research on political parties in journals including the European Journal of Political Research, West European Politics and Party Politics. He has also coedited the volumes Europe’s Radical Left from Marginality to Mainstream (edited, 2016) and the Routledge Handbook of Political Parties (forthcoming). Luke March is Professor of Post-Soviet and Comparative Politics, University of Edinburgh, UK. Key publications include The Communist Party in Post-Soviet Russia (2002), Radical Left Parties in Europe (2011), Europe’s Radical Left: From Marginality to the Mainstream (edited, 2016) and The European Left Party (with R. Dunphy 2019). .